ANALISIS MINAT DAN MOTIVASI PESEPAKBOLA PUTRI U16 DI KABUPATEN BATANG JAWA TENGAH - Ridwan Firmansah, Sandy; Wiyanto, Agus; Pratama, Dani Slamet (Fakultas Ilmu Keolahragaan Unimed, 2025)
This study aims to analyze the level of interest and motivation of U16 female footballers in the Kencana Muda FC Team in Kenconorejo Village, Batang Regency, Central Java. The method used is descriptive quantitative with a population of all U16 players totaling 23 people and sampled through a saturated sampling technique. The research instrument was a questionnaire with a five-point Likert scale consisting of 24 statements related to interest and motivation, and observations as supporting data. The results showed that the level of player interest was in the very high category with a percentage of 93.7%, especially in the indicators of interest and desire to be involved (97.4%). Player motivation was also in the very high category with a percentage of 93.3%, with the highest scores in the indicators of enjoyment (97.0%) and challenge/self-development (96.1%). These findings indicate that intrinsic motivation is more dominant than extrinsic motivation. Overall, very high interest and motivation are important assets in the development of early-age female football, and can be the basis for formulating more effective and sustainable development strategies.